THE 50 M FREE STYLE SWIMMING STROKE SPEED IMPROVEMENT BY USING HAND PADDLE SWIM AND PARACHUTE SWIM - Muhammad Chusaini; Hari Setijono; Edy Mintarto (Program Pascasarjana Universitas Negeri Jakarta, 2020)
Swimming is the basic ability of every living being. Consciously and unconsciously, we have already done this activity even since we were not born yet. However, once human was born, some of creatures lose their ability to swim. A well-structured training is necessary to emerge one's swimming potential. Currently, there are many Olympiads and competition for swimming. The most common aspect in swimming competition is the speed. In order to obtain the maximum swimming speed, a special training program is essentially needed. This research used hand paddle swim and parachute swim training program to increase arm muscles' power and swimming speed. The result obtained was hand paddle swim and parachute swim training program were able to increase arm muscles' power and swimming speed.